Influence Learning Model Predict Discuss Explain Observe Discuss Explain (PDEODE) Literacy of Science Literacy Against Learning Competencies Learners on Biology Subjects Class X SMAN 1 2x11 Kayutanam - Cici Putri Sari; S. Syamsurizal (Universitas Negeri Padang, 2018)
This research is based on the low competence of biology learners learners. Factors that affect the low competence of learners learning is the process of learning by teachers and learners in the classroom is still centered on the teacher, the lack of interaction between students with teachers, and learning competence of learners has not been achieved in accordance with minimal mastery criteria (KKM). The purpose of this research is to know the influence of predictor learning model explain explain observe discuss explain (PDEODE) containing science literacy to learners' competence in the subjects of biology class X SMAN 1 2X11 Kayutanam. This research is a quasi experimental research with randomized control group design posstest only design. Sampling from population using purposive sampling technique that class X1 as experiment class and class X3 as control class. The data analysis technique used to test the hypothesis is t test. Learning competencies analyzed are learning competence in the cognitive, affective, and psychomotor aspects with environmental change materials. The results showed that the average value of posstest learning competence on the cognitive, affective and psychomotor aspects of the experimental class students higher than the control class. So it can be concluded that the application of predictor learning explain explain observe discuss explain (PDEODE) model of science literacy improves the cognitive, affective, and psychomotor learners' competence in the material of environmental change.